KEMITRAAN DAN KEUNTUNGAN USAHA PENANGKARAN BENIH PADI: STUDI KASUS PADA CV MAJU SEJAHTERA INTI - Hanun, Salma Arifah; Endaryanto, Teguh; Marlina, Lina (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2024)
This study aimed to examine business partnerships and analyze the profitability of rice seed breeding at CV Maju Sejahtera Inti (CV MSI). The research employed a case study approach, conducted at CV MSI in Central Lampung Regency. This company is notable for its extensive farmer network, spanning several districts in Lampung Province, and its involvement in the rice seed breeding business. Respondents included the owners and employees of CV MSI. Data collection was conducted from November to December 2023. Business partnerships were analyzed using an interactive descriptive qualitative model. Profitability was assessed using the R/C ratio for the Goal, Mentes, and Marqy seed brands over two planting seasons in 2022–2023. The results showed that the business partnership between farmers and the company followed a sub-contract model. The R/C ratios based on cash costs for the three seed brands were 1.21 for Mentes, 1.13 for Goal, and 1.13 for Marqy, respectively. Key words:  Partnership, Profits, R/C ratio, Rice Seed